A new species of Fejervarya Bolkay, 1915 (Anura: Dicroglossidae) from the northern Western Ghats parts of Maharashtra, India - Phuge, Samadhan; Dinesh, K.p.; Andhale, Ramnath; Bhakare, Kalyani; Pandit, Radhakrishna (Zootaxa, 2019)
In the recent past the systematic position and taxonomy of genus Fejervarya, Bolkay is undergoing changes in its systematic position due to fairly good amount of phylogenetic resolution, cryptic morphological characters and lack of systematic sampling for phylogenetic studies across the range of distribution. In our sampling in the northern Western Ghats, we encountered a new lineage sister to the phylogenetic cluster which comprises the 'Rufescens complex'. This new lineage is described here as new species Fejervarya marathi sp. nov. based on distinctness in a combination of morphological characters, genetic distance and geography. The problems in morphological groupings for the Fejervarya frogs of the Western Ghats in the recent studies are discussed with the sub-clade composition based on geography in the phylogenetic tree.